Investigation of the N-Glycosylation of the SARS-CoV-2 S Protein Contained in VLPs Produced in Nicotiana benthamiana - Juliette Balieu; Jae-Wan Jung; Philippe Chan; George P. Lomonossoff; Patrice Lerouge; Muriel Bardor (Molecules, 2022)
The emergence of the SARS-CoV-2 coronavirus pandemic in China in late 2019 led to the fast development of efficient therapeutics. Of the major structural proteins encoded by the SARS-CoV-2 genome, the SPIKE (S) protein has attracted considerable research interest because of the central role it plays in virus entry into host cells. Therefore, to date, most immunization strategies aim at inducing neutralizing antibodies against the surface viral S protein. The SARS-CoV-2 S protein is heavily glycosylated with 22 predicted N-glycosylation consensus sites as well as numerous mucin-type O-glycosylation sites. As a consequence, O- and N-glycosylations of this viral protein have received particular attention. Glycans N-linked to the S protein are mainly exposed at the surface and form a shield-masking specific epitope to escape the virus antigenic recognition. In this work, the N-glycosylation status of the S protein within virus-like particles (VLPs) produced in Nicotiana benthamiana (N. benthamiana) was investigated using a glycoproteomic approach. We show that 20 among the 22 predicted N-glycosylation sites are dominated by complex plant N-glycans and one carries oligomannoses. This suggests that the SARS-CoV-2 S protein produced in N. benthamiana adopts an overall 3D structure similar to that of recombinant homologues produced in mammalian cells.